ANALISIS LC-MS/MS SENYAWA METABOLITE EKSTRAK DAUN PUTAT (Planchonia valida) DAN PREDIKSI POTENSINYA SEBAGAI KANDIDAT OBAT ANTIKANKER - Dewi, Tribuana Tungga; Bela, Anisa; Prabawa, Satria; Latief, Madyawati; Tarigan, Indra Lasmana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Secondary metabolite compounds contained in plants are bioactive substances related to the chemical content in plants, so that some plants can be used as medicinal materials. Putat (Planchonia valida) is a medicinal plant that has bioactive compounds that have potential as anticancer. Compound analysis of LC-MS test results has been carried out which shows several metabolite compounds contained in putat. The method used is analyzing compounds obtained from LC-MS results, screening compounds using pchembl and chemspider websites. And using the pChEMBL webserver to find out the bioactivity of these compounds. The purpose of this study is to determine and predict the potential bioactivity of the compounds contained therein as new drug candidates. The results obtained from this study are metabolite compounds in putat have the potential as anticancer based on the screening results carried out using the pChEMBL webserver by looking at the highest pIC50 value, obtained the highest pIC50 value of 8.18 with target proteins namely Serine/threonin mTOR and Cholinesterase which are target proteins that have anticancer activity.